2013
DOI: 10.1083/jcb.201301072
|View full text |Cite
|
Sign up to set email alerts
|

The Bruchpilot cytomatrix determines the size of the readily releasable pool of synaptic vesicles

Abstract: Two Bruchpilot isoforms create a stereotypic arrangement of the cytomatrix that defines the size of the readily releasable pool of synaptic vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
129
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 53 publications
(110 reference statements)
5
129
0
Order By: Relevance
“…Based on the present finding that N D and N C are equal, we propose that, at PF-MLI synapses, either 0 or 1 fusion-competent SV is docked per VGCC cluster. This model is similar to the proposed association of precisely defined docking sites with a cluster of cacophony channels at the fly neuromuscular junction (23,24) with the important difference that, in the fly, several docking sites are associated with one VGCC cluster, whereas we propose here a one-to-one stoichiometry.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Based on the present finding that N D and N C are equal, we propose that, at PF-MLI synapses, either 0 or 1 fusion-competent SV is docked per VGCC cluster. This model is similar to the proposed association of precisely defined docking sites with a cluster of cacophony channels at the fly neuromuscular junction (23,24) with the important difference that, in the fly, several docking sites are associated with one VGCC cluster, whereas we propose here a one-to-one stoichiometry.…”
Section: Discussionmentioning
confidence: 73%
“…Another remaining source of uncertainty concerns SV supply. Docking-site replenishment is a Ca 2+ -driven process (3) that depends on filament-like links between SVs and plasma membrane (20,24,56,57), possibly involving actin and myosin II (58)(59)(60)(61). In PF-MLI synapses, recent results indicate that an empty docking site is resupplied by a replacement SV that moves toward the docking site by a cytoskeleton-driven transition (twostep model) (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Brp C terminus is important for SV tethering, as an allele that lacks the C-terminal 17 amino acids (brp nude ) shows an impairment in SV tethering near T-bars (Hallermann et al 2010). Two isoforms of Brp appear to be arranged in an alternating circular pattern that is important for normal T-bar structure and SV tethering (Matkovic et al 2013). Furthermore, quantitative inferences about CAZ substructure and stoichiometry were made using data from stochastic optical reconstruction microscopy (dSTORM), which can provide information on the distribution of single molecules (Ehmann et al 2014).…”
Section: The Active Zone Cytomatrixmentioning
confidence: 99%
“…Another presynaptic protein extensively studied with STED microscopy is the Drosophila melanogaster ELKS family protein Bruchpilot (BRP), which forms the electron-dense active zone cytomatrix. Following an early study where the doughnut-like structure was shown for the first time [10], two-color STED microscopy was applied, making apparent a substructure of two different isoforms appearing in an alternating array of clusters [11]. After studying isoform-specific mutants these authors proposed that the size of the Bruchpilot cytomatrix determines the size of the readily releasable pool of synaptic vesicles.…”
Section: Imaging Presynaptic Proteinsmentioning
confidence: 99%